PENGARUH KUALITAS SUMBER DAYA MANUSIA DAN LINGKUNGAN KERJA TERHADAP KINERJA DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI DI BADAN PENANGGULANGAN BENCANA DAERAH KABUPATEN KUTAI TIMUR - Kusnandi; Ausy Riana; Juwita Aprillia; Jumri (Journal Competency of Business, 2025)
This research to analyze the effect of human resource quality and work environment on employee performance, with job satisfaction serving as a mediating variable at the Regional Disaster Management Agency of East Kutai Regency. The research employed a quantitative explanatory approach, and data were collected through questionnaires distributed to employees. Data analysis was conducted using SmartPLS to evaluate validity, reliability, direct relationships, and indirect effects among variables. The findings indicate that human resource quality has a positive and significant effect on employee performance, while the work environment does not have a significant direct effect on performance. Human resource quality does not significantly affect job satisfaction, whereas the work environment has a positive and significant effect on job satisfaction. Job satisfaction also has a positive and significant effect on employee performance. Furthermore, the mediation analysis reveals that job satisfaction does not mediate the relationship between human resource quality and employee performance but successfully mediates the relationship between the work environment and employee performance. The study concludes that improving employee performance requires strengthening employee competencies, creating a supportive work environment, and enhancing job satisfaction to achieve organizational objectives effectively.